2021
DOI: 10.1002/ajb2.1689
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐linked gene expression and the emergence of hermaphrodites in Carica papaya

Abstract: Premise One evolutionary path from hermaphroditism to dioecy is via a gynodioecious intermediate. The evolution of dioecy may also coincide with the formation of sex chromosomes that possess sex‐determining loci that are physically linked in a region of suppressed recombination. Dioecious papaya (Carica papaya) has an XY chromosome system, where the presence of a Y chromosome determines maleness. However, in cultivation, papaya is gynodioecious, due to the conversion of the male Y chromosome to a hermaphroditi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…For instance, Carica papaya (Caricaceae) is a dioecious tree with XY homomorphic sex chromosomes that evolved approximately 7 Ma [92]. Evidence for DC was only found for a few non-recombining X/Y genes (7 out of 50) [93], and partial DC was found for some X-hemizygous genes (electronic supplementary material, table S2) [94].…”
Section: Common Patterns Of Incomplete Dosage Compensation In Other P...mentioning
confidence: 99%
“…For instance, Carica papaya (Caricaceae) is a dioecious tree with XY homomorphic sex chromosomes that evolved approximately 7 Ma [92]. Evidence for DC was only found for a few non-recombining X/Y genes (7 out of 50) [93], and partial DC was found for some X-hemizygous genes (electronic supplementary material, table S2) [94].…”
Section: Common Patterns Of Incomplete Dosage Compensation In Other P...mentioning
confidence: 99%
“…If they do, the initial sterility factors should be within the oldest non-recombining region, or stratum, and other such factors might be found in younger strata, consistent with being associated with recombination suppression. In papaya, however, even though a young stratum has evolved, neither the sex chromosome as a whole, nor its fully Y-linked part, is enriched with genes whose expression in males is higher than in females [31]. However, this study found one Y-linked gene with lower expression in hermaphrodites than males, making it a good candidate for the active female-suppressing factor.…”
Section: Recombination Suppression and Master Sex-determining Genesmentioning
confidence: 79%
“…For example, in several fish, crossovers in male meiosis are strongly localized to the chromosome ends [16,28]; the centromere locations must then correspond to the non-crossover ends. Combined genetic and physical maps are still scarce for plants, but the small Y-linked region in Carica papaya is near the genetic centromere location of the metacentric chromosome 1 [2931] (figure 3), though part stopped recombining more recently [32].
Figure 3Example of a completely sex-linked region close to a plant centromeric region with a low recombination rate.
…”
Section: Identifying Sex-linked Regions From Linkage Disequilibriamentioning
confidence: 99%
“…Additionally, FMO3 , ATPD , WRKY21 , and exostosin are located in the sex-determined region of plants with unknown specific functions [ 148 , 176 , 214 ]. Their specific functions need further study.…”
Section: Discussionmentioning
confidence: 99%